WIND TOWERS – DESIGN OF FRICTION CONNECTIONS FOR ASEMBLING SECTIONS OF TUBULAR STEEL TOWERS - Fric, Nenad; Gligić, Boris; Dobrić, Jelena; Marković, Zlatko (Journal of Applied Engineering Science, 2012)
The towers represent about 15 to 20% of the total installation costs and optimized design may therefore lead to substantial savings with regard to costs and use of materials. Some of the most interesting design and manufacturing details are connections used to assemble sections of tubular steel towers supporting wind turbins. There is traditional flange ring connection and on the other side, as a new proposal, friction connection. In this paper theoretic basis of design of friction connection of wind towers is given. Key words: Wind tower, friction connection, tension controled bolts, friction surfaces